CH and C2 radicals characterization in natural gas turbulent diffusion flames - Martins, C. A.; Pimenta, A. P.; Carvalho, J. A. [UNESP]; Ferreira, M. A.; Caldeira-Pires, A. A. (Springer Nature, 2005)
This paper reports the construction of an axisymmetric nonpremixed piloted jet burner, with well-defined initial and boundary conditions, known as the Delft burner, to assess turbulence-chemistry interaction in non-premixed turbulent flames. Detailed experimental information is described, involving hot-wire anemometry, thin-wire thermocouples and chemiluminescence visualization measurements. Radial profile of the axial mean velocity indicates excellent agreement between flow patterns developed within Delft installation and the one described herein. Chemiluminescence emissions from CH and C2 free-radicals were acquired with a CCD camera. Tomography reconstruction analysis was utilised to compare radical emissions and temperature spatial distributions. There was a strong dependence between temperature and CH/C 2 emissions. This is an indication that these radicals can be used in flame front studies.
Keywords: Flame tomography; Flame turbulence; Gaseous fuel diffusion flames; Thin-wire termocouples; Carbon; Diffusion; Flammability; Free radicals; Jets; Natural gas; Nozzles; Thermocouples; Tomography; Turbulent flow; Thin wire thermocouples; Gas burners